Observational case-control study of small-fiber neuropathies, with regards on smoking and vitamin D deficiency and other possible causes - Fouchard, Maxime; Brenaut, Emilie; Genestet, Steeve; Ficheux, Anne-Sophie; Marcorelles, Pascale; Misery, Laurent (Frontiers in Medicine, 2023)
Introduction Small fiber neuropathies (SFNs) are disorders of skin nerve endings inducing pruritus, burning pain, numbness, and paresthesia. The aims of this study were to search for putative etiologies of SFN and their occurrence in a cohort of patients and to compare patients with SFN to a group of patients without SFN to highlight potential factors associated with SFN. Methods This study was observational, retrospective, and monocentric. All patients with symptoms of SFN who underwent skin biopsies with intraepidermal nerve density counts were included. Patients with a count lower than 5 percentiles were considered to be in the SFN group. Other patients were considered to be the control group. Results A total of 162 patients with SFN and 161 controls were included. No cause was identified for 108 patients (61.7%). The established causes were autoimmune diseases (9.1%), diabetes or glucose intolerance (8%), medication (4%), liver disease (3.4%), and monoclonal gammopathy of undetermined significance (2.9%). Current or former smokers were more numerous in the SFN group (26.5%) than in the control group (16.1%), while vitamin D amounts were significantly lower in the SFN group than in the control group. Discussion Hence, tobacco smoking and vitamin D deficiency might be new putative causes of SFN.